Challenges in adjustability and mechanism: analysis on results obtained with maxillary appliances for moderate obstructive sleep apnea - Thibault Canceill; Laura Pascalin; Anne Decotte; Guillaume De Bonnecaze (Trials)
Abstract Comment on “Comparative evaluation of the efficacy of customized maxillary oral appliance with mandibular advancement appliance as a treatment modality for moderate obstructive sleep apnea patients.”